Factors affecting the market value of commercial banks listed on the Amman Stock Exchange - bouaziz, azhar (Finance and Business Economies Review, 2020)
this study aimed to figure it out the factors affecting the market value of the commercial banks listed on the Amman Stock Exchange, where the study was conducted on a sample of 13 commercial banks during the period from 2005 to 2018, using panel data to study the impact of independent variables (stock turnover, return on assets, return on equity, ownership percentage, debt ratio, cash liquidity ratio, bank size and trading volume) on the dependent variable is the market value of the commercial banks under study. The results indicated that there was a significant positive impact for each of the return on assets, the cash liquidity ratio, the bank’s size and the trading volume on the market value and a significant negative impact of the share turnover rate, the return on equity and the ownership ratio, and the study also found that there was no significant effect of the debt ratio on the market value of commercial banks.